Răspuns :
Explicație pas cu pas:
b)
[tex] {15}^{2} {}^{x} \times 15 {}^{ - 3} = 3 {}^{x} \times 5 {}^{3x - 6} [/tex]
[tex]15 {}^{2} {}^{x} \times 15 { - }^{3} = {3}^{x} \times {5}^{3} {}^{x} \times 5 { - }^{6} [/tex]
[tex]225 {}^{x} \times 15 { - }^{3} = {3}^{x} \times {5}^{3} {}^{x} \times {5}^{ - 6} \\ 225 {}^{x} \times \frac{1}{15 {}^{3} } = 3 {}^{x} \times {5}^{3 {}^{x} } \times {5}^{ - 6} \\ 225 {}^{x} \times \frac{1}{15 {}^{3} } = 3 {}^{x} \times 125 {}^{x} \times 5 {}^{ - 6} [/tex]
Atata stiu cred ca ti am fost de ajutor